Kalimat Larangan: Kajian Struktur dan Fungsinya dalam Penafsiran Al-Qur’an - Husnul Khatimah; Andi Miswar; Mohamad Harjum (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The prohibitive expression (al-nahy) is one of the forms of inshā’ ṭalabī (directive speech) that plays a significant role in understanding the meanings of the Qur'an and the formulation of Islamic legal rulings (aḥkām shar‘iyyah). This study aims to analyze the grammatical structure and functions of prohibitive expressions in Qur'anic interpretation through a library research approach using a descriptive-analytical method. The findings reveal that prohibitive expressions appear in several forms, namely the imperfect verb (fi‘l muḍāri‘) preceded by lā al-nahy (the prohibitive lā), the direct use of prohibitive expressions, and the use of the word ḥarrama ("has prohibited" or "has made unlawful"). According to the principles of uṣūl al-fiqh, al-nahy fundamentally denotes prohibition (taḥrīm), requires immediate compliance, and remains permanently applicable unless there is evidence indicating otherwise. However, in certain contexts, prohibitive expressions may function beyond their primary meaning, serving as supplication (du‘ā’), request (iltimās), guidance (irshād), continuity (dawām), explanation of consequences (bayān al-‘āqibah), expression of despair (ta’yīs), and threat (tahdīd). A proper understanding of the structure and functions of prohibitive expressions is therefore essential for Qur'anic exegetes in order to avoid errors in deriving legal rulings (istinbāṭ al-aḥkām) and to comprehend the intended meanings of Allah comprehensively.